Visceral Vessels and Aortic Repair 2019
DOI: 10.1007/978-3-319-94761-7_12
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Open Reconstruction of Hilar Renal Artery Aneurysms: A Single-Center Experience

Abstract: The renal artery aneurysms (RAAs) represent 3% of all visceral aneurysms. Their incidence rate is about 0.1% in the general population [1], even if angiographic findings report a little higher incidence (0.3-2.5%) [2] with a modest prevalence in female patients. RAAS are mainly detected in the sixthseventh decade, and female patients are associated with an earlier incidence [3]. True RAAs are extra-parenchymal in 90% of cases, while intraparenchymal RAAs represent 10% of cases, and they are often multiple and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Although the natural course of HRAAs is undetermined, the surgical indications for the treatment of HRAA are an enlarged renal arterial diameter of >2 cm, female sex and childbearing age, and symptoms such as flank pain, hematuria, refractory hypertension, thromboembolism, dissection, and rupture. 1 , 3 , 8 In the present case, the patient was cured by endovascular therapy.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Although the natural course of HRAAs is undetermined, the surgical indications for the treatment of HRAA are an enlarged renal arterial diameter of >2 cm, female sex and childbearing age, and symptoms such as flank pain, hematuria, refractory hypertension, thromboembolism, dissection, and rupture. 1 , 3 , 8 In the present case, the patient was cured by endovascular therapy.…”
Section: Discussionsupporting
confidence: 52%
“…Among the reported cases, four patients had a solitary kidney, two patients were pregnant, and two repaired kidneys were successfully transplanted to two men, respectively, which provided benefits to both donors and recipients. 5 , 8 , 10 , 11 , 13 19 After analysis of the therapeutic strategies, we found that 47% ( N = 26) of HRAAs were treated by ex vivo reconstruction (EVR), 44% ( N = 24) were treated by in situ reconstruction (ISR), 5% ( N = 3) were treated by endovascular therapy, and 4% ( N = 2) were treated with nephrectomy. Laparoscopy was used to reduce surgical trauma owing to its lower invasiveness, and 17% ( N = 9) of the operations were performed with the aid of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential mechanism is due to turbulent flow in the renal artery and increased renin production; other theories include concomitant renal artery stenosis, kinking of the renal artery, and distal embolization to the renal parenchyma. 2 Although the mechanism is unclear, it has been noted that some patients have had improved hypertension after treatment, but despite this, it is not considered to be a treatment indication. 3,4 Symptoms related to RAA can depend on the type of aneurysm and its location.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 A small portion of the extraparenchymal aneurysms include hilar RAAs, which occur at the distal portion of the renal artery. 2 Although these aneurysms are considered extraparenchymal, they are often close to the hilum and require more complex interventions.…”
Section: Discussionmentioning
confidence: 99%